Biological activities and phytochemical constituents of mace extract derived from Endocomia macrocoma - Ali , Saadi Albaer; Anumol, P S; Nimmi , Varghese; Enrika, Joy Ajit; Aadithye, R Nair; Gangaprasad, A; Viji, Vijayan (Plant Science Today, 2025)
This study explores the phytochemical composition and biological activity of petroleum ether extract (PEEM) derived from the mace of Endocomia macrocoma. Methods employed include qualitative phytochemical screening, HPTLC, GC-MS, LC-MS, as well as free radical scavenging and antimicrobial assays. Preliminary screening revealed the presence of terpenoids, glycosides, alkaloids and tannins. Antioxidant activity was confirmed via HPTLC-DPPH and ABTS assays showing yielding IC₅₀ values of 143.68 ± 2.82 μg/mL and 105.28 ± 1.36 μg/mL, respectively. As the first comprehensive analysis of E. macrocoma mace, this study highlights its potential as a natural source of antioxidants and antimicrobial agents, supporting traditional medicinal use and offering prospects for pharmaceutical development.